How not to get stuck in the middle lessons for the commonwealth of independent states from Central and Eastern Europe - Kamil Pruchnik; Jakub Zowczak (Center for Social and Economic Research (CASE), 2017)
The aim of this paper is to analyze how different models of transformation in Central and Eastern Europe (CEE) and the Commonwealth of Independent States (CIS) increased or decreased the risk of being stuck in the middle-income trap (MIT). The key finding is that the CEE and CIS countries are, from a definition point of view, not materially at risk of the MIT as out of nine selected MIT definitions, none of the CEE or CIS countries were "stuck" more than three times. At the same time, the CEE countries are more at risk of falling into the MIT than the CIS countries; however this is because the CIS is a poorer region and is not near the lower MIT thresholds. The CEE countries had a better start at the beginning of the transformation and on average implemented a better set of transformation models; however, some CEE countries are now struggling to permanently join the advanced countries and CIS countries are, on average, far behind that. The literature review on transformation models and the analysis of the "jumps" in the World Bank ranking classification suggest that while the MIT is not a concern for CEE or CIS countries, in order to speed up convergence, CIS countries might consider more shocks and consistently following free market related approaches. The study fills a gap in the literature on the MIT which has thoroughly analyzed the Asian and Latin American countries but has provided little analysis of the CEE and CIS countries.
Keywords: O43; P20; P11; P16; B15; 330; middle income trap; convergence; transition; transformation